2019
DOI: 10.1021/acscatal.8b04946
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric, Nearly Barrierless C(sp3)–H Activation Promoted by Easily-AccessibleN-Protected Aminosulfoxides as New Chiral Ligands

Abstract: Although chiral sulfoxides are important motifs in medicinal chemistry and asymmetric synthesis, design and applications of sulfoxide ligands are still limited, in particular in the context of asymmetric C−H activation. We disclose herein the conception and synthesis of enantiopure N/S ligands: N-protected aminosulfoxides. The potential of these auxiliaries in asymmetric C(sp 3 )−H activation is demonstrated as high enantioselectivity is reached during a Pdcatalyzed direct arylation of cyclopropane carboxylic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 94 publications
2
31
0
Order By: Relevance
“…The agostic CAr-HAr…metal interaction is characterized by an attractive ring and associated with an attractive domain materializing the C=Op…HAr interaction that plays a central role in TS-CH. It was already stated previously 49,92 that this NCI pattern -or configuration -was the sine qua non condition for the "internal" CMD mechanism to be effective. Analysis of Bader charges (a.k.a.…”
mentioning
confidence: 80%
“…The agostic CAr-HAr…metal interaction is characterized by an attractive ring and associated with an attractive domain materializing the C=Op…HAr interaction that plays a central role in TS-CH. It was already stated previously 49,92 that this NCI pattern -or configuration -was the sine qua non condition for the "internal" CMD mechanism to be effective. Analysis of Bader charges (a.k.a.…”
mentioning
confidence: 80%
“…Another recent example that highlights the important role that π–π interactions between substrate and ligand can play was reported by Wencel-Delord, Colobert, and co-workers in the palladium-catalyzed direct arylation of cyclopropanes using a bidentate S/N ligand ( Figure 43 a,b). 157 Detailed DFT calculations suggested that a π–π interaction between the aromatic perfluoroarene of the substrate and the aromatic group on the ligand is important in precisely controlling substrate orientation. When the N -acetyl group of the palladium complex comes into close proximity with the substrate, C–H activation takes place via the CMD mechanism.…”
Section: Carbon–carbon Bond-forming Reactionsmentioning
confidence: 99%
“…In more complex cases, the analysis of deformation density plots provides detailed information on the local or remote orbitals donating and accepting electron density upon build‐up of a given set of bonds between two intramolecular fragments that have to be judiciously chosen. The same fragmentation scheme implying closed shell fragments in the previous EDA was used for 4a and 4b .…”
Section: Theoretical Investigationmentioning
confidence: 99%
“…Non‐covalent interactions play a central role in Chemistry and particularly in the cohesion of small to large molecular coordination and organometallic complexes Their role in organometallic chemistry is growingly being investigated to rationalize the interplay between the ligand retinue and its metal centre in important processes of homogeneous catalysis such as C‐H bond activation. [1c], In 2013, we defined the concept of “hemichelation”; as a genuine mode of coordination of polytopic ligands to metal centres allying covalent and non‐covalent binding interaction. In this situation, at least one site of coordination is formally left covalently‐unbound and favoured over other coordination scenarios .…”
Section: Introductionmentioning
confidence: 99%